Pemanfaatan Zotero dalam Penyusunan Karya Tulis Ilmiah Pustakawan - Hary Supriyatno (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2018)
In addition to provide excellent service, a librarian should also be able to pour ideas in writing. Writing scientific papers has become a mandatory duty for librarians not only when dealing with job promotion. It is a challenging task since one need to do preparation and have a focus in writing. Apart from having ideas and themes in the study, librarians need to be supported by quality reference materials. In this case, Zotero became the best solution to assist librarians when preparing scientific works. It helps them to obtain quality reference materials as well as to manage the references. Zotero’s ease of installation and its data management features make the software easier to operate and therefore highly recommended to be used for managing citations.